The mediating effect of self-criticism on college students' emotion dysregulation and intention to self-harm - Jannah, Saffirah Rahayu; Yuliadi, Istar; Scarvanovi, Berliana Widi (Psikohumaniora: Jurnal Penelitian Psikologi, 2022)
College students are in a period of instability, which may be stressful and put them at risk of developing the intention to self-harm. This study examines the effect of self-criticism as a mediator in the association between emotion dysregulation and the intention to self-harm. Quantitative research was conducted on 354 students aged 18-23 years, using the disproportionate cluster random sampling technique. The instruments used were an intention to self-harm scale, self-criticism scale, and emotion dysregulation scale. The results from the mediation analysis conducted using the PROCESS program of Hayes shows that self-criticism significantly mediates the association between emotion dysregulation and students' intention to self-harm (ab = .39, BootSE = .05, 95% BootCI [.29 to .48]). Nevertheless, the results also suggest that even after accounting for the mediating effect of self-criticism, emotion dysregulation still positively impacts students' intention to self-harm (c' = .14, p = .017). The implications of the findings provide insights for college students and all the parties involved with them regarding the mechanisms behind the intention to self-harm.